2019
DOI: 10.3892/ol.2019.10723
|View full text |Cite
|
Sign up to set email alerts
|

Identification of differentially expressed genes between primary lung cancer and lymph node metastasis via bioinformatic analysis

Abstract: Lung cancer (LC), with its high morbidity and mortality rates, is one of the most widespread and malignant neoplasms. Mediastinal lymph node metastasis (MLNM) severely affects postoperative survival of patients with LC. Additionally, the molecular mechanisms of LC with MLNM (MM LC) remain not well understood. To identify the key biomarkers in its carcinogenesis and development, the datasets GSE23822 and GSE13213 were obtained from the Gene Expression Omnibus database. The differentially expressed genes (DEGs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 64 publications
2
2
0
Order By: Relevance
“…From GO analysis, DEGs in milk EVs from BLV-infected cattle were revealed to be meaningfully involved in major molecular functions, biological processes, and cellular components, and were categorized in distinct protein classes including cellular processes, metabolic processes, response to stimuli, cells, catalytic activity, binding, extracellular regions, and so on. These findings were consistent with those from previous studies, which had revealed EVs from many tumors/cancers to be engaged in various biological functions, such as immune modulatory features, protein binding, signal transduction, and so on [46][47][48]. The previous study reported that during BLV infection, gene involved in diverse biological procedure including cellular proliferation, innate immune response, and metabolic process [49].…”
Section: Discussionsupporting
confidence: 92%
“…From GO analysis, DEGs in milk EVs from BLV-infected cattle were revealed to be meaningfully involved in major molecular functions, biological processes, and cellular components, and were categorized in distinct protein classes including cellular processes, metabolic processes, response to stimuli, cells, catalytic activity, binding, extracellular regions, and so on. These findings were consistent with those from previous studies, which had revealed EVs from many tumors/cancers to be engaged in various biological functions, such as immune modulatory features, protein binding, signal transduction, and so on [46][47][48]. The previous study reported that during BLV infection, gene involved in diverse biological procedure including cellular proliferation, innate immune response, and metabolic process [49].…”
Section: Discussionsupporting
confidence: 92%
“…Genetic factors are probably relevant in a subset of lung cancer patients with lymph node metastasis [17,18]. The previous study has shown the FAM136A mRNA level was significantly higher in lung carcinoma tissues than the normal lung tissues [19], which is in good agreement with our present findings.…”
Section: Discussionsupporting
confidence: 93%
“…Structurally, N-terminal Eps15 homology (EH1 and EH2) domains, a coiled coil region, and five SH3 domains are present in the short isoform (ITSN-S), while the long isoform of ITSN (ITSN-L) has an additional C-terminal DH/PH domain, which confers GEF activity (Hunter et al, 2013). Even though low expression of ITSN1 was recently correlated with higher grade in breast and lung cancer (Xie et al, 2019;Zhang and Zhang, 2019), A role for ITSN in neuroblastoma has been shown by a study where knockdown of ITSN decreased orthotopic neuroblastoma growth in mice (Harris et al, 2017).…”
Section: Targeting Intersectin (Itsn)mentioning
confidence: 99%